Effective coverage of antenatal care services in Ethiopia: a population-based cross-sectional study - Zewditu Abdissa; Kassahun Alemu; Seblewengel Lemma; Della Berhanu; Atkure Defar; Theodros Getachew; Joanna Schellenberg; Tanya Marchant; Solomon Shiferaw; Amare Tariku; Tadesse Guadu; Girum Taye; et al. (BMC Pregnancy and Childbirth, 2024)
Abstract Background Antenatal care (ANC) is a principal component of safe motherhood and reproductive health strategies across the continuum of care. Although the coverage of antenatal care visits has increased in Ethiopia, there needs to be more evidence of effective coverage of antenatal care. The 'effective coverage' concept can pinpoint where action is required to improve high-quality coverage in Ethiopia. Effective coverage indicates a health system's performance by incorporating need, utilization, and quality into a single measurement. The concept includes the number of contacts, facility readiness, interventions received, and components of services received. This study aimed to measure effective antenatal care coverage in Ethiopia. Methods A two-stage cluster sampling method was used and included 2714 women aged 15–49 years and 462 health facilities from six Ethiopian regions from October 2019 to January 2020. The effective coverage cascade was analyzed among the targeted women by computing the proportion who received four or more antenatal care visits where the necessary inputs were available, received iron-folate supplementation and two doses of tetanus vaccination according to process quality components of antenatal care services. Results Of all women, 40% (95%CI; 38, 43) had four or more visits, ranging from 3% in Afar to 74% in Addis Ababa. The overall mean health facility readiness score of the facilities serving these women was 70%, the vaccination and iron-folate supplementation coverage was 26%, and the ANC process quality was 64%. As reported by women, the least score was given to the quality component of discussing birth preparedness and complication readiness with providers. In the effective coverage cascade, the input-adjusted, intervention-adjusted, and quality-adjusted antenatal coverage estimates were 28%, 18%, and 12%, respectively. Conclusion The overall effective ANC coverage was low, primarily due to a considerable drop in the proportion of women who completed four or more ANC visits. Improving quality of services is crucial to increase ANC up take and completion of the recommended visits along with interventions increasing women’s awareness.